11 - Shona Traditional Religion and Medical Practices: Methodological Approaches to Religious Phenomena - Shoko, Tabona (Africa Development, 2021)
This article reviews select principal literature on traditional religion and medical practices in Zimbabwe with a view to demonstrating how this subject has been dealt with through the contributions of scholars from a variety of disciplines. In so doing, it paves the way for phenomenol- ogy, which is the alternative approach used in this study. The article explores the relationship between anthropology and sociology as used by previous scholars to study religion and medicine in the context of the Shona pe ple in Zimbabwe on the one hand, and phenomenology on the other.